Протидія міліції УСРР крадіжкам коней (конокрадству) у 1920-ті роки - Греченко, В. А.; Grechenko, V. A.; ORCID: http://orcid.org/0000-0002-6046-0178 (Право і безпека. - 2016. - № 1 (60). - С. 20-23, 2016)
Розглянуто досвід боротьби з крадіжкою коней в Україні у період нової економічної політики. Крадіжка коней була одним з поширених і тяжких злочинів, оскільки коні в той час були одними з головних засобів виробництва в сільському господарстві. Відзначено, що результативність діяльності щодо боротьби з конокрадством прямо залежала від організації роботи міліції.

The experience of combating horsestealing by militia in Ukraine during the period of the New Economic Policy has been studied. Previously published studies on the history of the militia activities in combating crime during NEP period just mention some facts about this type of crime. This is the first study of this problem in Ukraine. Therefore, the objective of the article – is a certain systematization of the material on this topic and summarizing relevant facts. Horsestealing was one of the widespread and serious offenses because the horses at the time were one of the main means of production in the sphere of agriculture. It is noted that the effectiveness of fighting against horsestealing directly depended on the organization of the militia activities. The level of disclosure of this type of crime at that period was the lowest, and it indicated that the problem remained acute and urgent. In fact, the militia could not solve it radically during 1920s. But until 1924, due to the focus on fighting against gang violence, militia did not pay necessary attention to horsestealing, although the counteraction was carried out, as evidenced by numerous facts. However, the situation remained difficult in the late 1920s, as indicated by periodic addresses to this issue by the Board NKVD of Ukrainian SSR and by the level of disclosure of this type of crime.

Рассмотрен опыт борьбы с хищением лошадей в Украине в период новой экономической политики. Кража лошадей была одним из распространённых и тяжких преступлений, поскольку кони в то время были одними из главных средств производства в сельском хозяйстве. Отмечено, что результативность деятельности по борьбе с конокрадством прямо зависела от организации работы милиции.
Counteracting horsestealing by militia of Ukrainian SSR in 1920s
Противодействие милиции УССР хищениям лошадей (конокрадству) в 1920-ые годы
Греченко, В. А. Протидія міліції УСРР крадіжкам коней (конокрадству) у 1920-ті роки / В. А. Греченко // Право і безпека. - 2016. - № 1 (60). - С. 20-23.
Grechenko, V.A. (2016), “Counteracting horsestealing by militia of Ukrainian SSR in 1920s” [“Protydiia militsii USRR kradizhkam konei (konokradstvu) u 1920-ti roky”], Pravo i Bezpeka, No. 1, pp. 20–23.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Історія. History. История; Кримінологія. Criminology. Криминология; Internal Affairs Agencies; органы внутренних дел; міліція; конокрадство; нова економічна політика; злочинність; новая экономическая политика; militia; horsestealing; New Economic Policy; crime; милиция; конокрадство; преступность